ANALISIS PENGELOLAAN DANA ZAKAT FITRAH SEBAGAI PEMBERDAYAAN EKONOMI UMAT - Novieati Dwi Lestari; Mega Novita Syafitri; Nuris Tishwanah; Nur Manna Silviyah (Ekonomi Islam, 2021)
Zakat is one of the fifth pillars of Islam and zakat is divided into two, namely zakat fitrah and zakat mal. Whereas Zakat fitrah is zakat issued by muzakki in the form of staple foodstuffs in accordance with the provisions, while zakat mal is zakat issued by muzakki in the form of goods or objects in accordance with the provisions and nishab. The purpose of writing this article is to determine the analysis of the management of zakat fitrah funds as an economic empowerment of the people. The research method used in writing this article is a qualitative research method, which is a method based on natural facts. The approach used is a descriptive approach that tends towards analysis by explaining what it is according to the data obtained. Keyword : Zakat Fitrah, Management Analysis, Community Economy